1992
DOI: 10.1093/ajcn/56.3.593
|View full text |Cite
|
Sign up to set email alerts
|

Parent-child relationships in nutrient intake: the Framingham Children's Study

Abstract: Nutrient intake affects many of the identified risk factors for coronary heart disease (CHD). Although CHD risk factors have been shown to aggregate within families, less is known about the familial aggregation of nutrient intake. We analyzed diet records for an average of 9 d per subject on 87 mothers, 83 fathers, and 91 children aged 3-5 y. A statistically significant but modest correlation (r less than 0.50) was found between parents' and children's intakes for most nutrients. The intake of nutrients was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
186
2
13

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 303 publications
(218 citation statements)
references
References 40 publications
17
186
2
13
Order By: Relevance
“…Associations in fat intake between parents and children as reported here were similar to some studies (Oliveria et al, 1992;Pe Ârusse et al, 1988;Lee & Kolonel, 1982;Eastwood et al, 1982) and high relative to other studies (Patterson et al, 1988;Laskarzewski et al, 1980;Nelson et al, 1980). Reported associations in fat intakes between husband and wives ranged between 0.38 and 0.58 in spouse pairs from North-America and the United Kingdom (Lee & Kolonel, 1982;Oliveria et al, 1992;Pe Ârusse et al, 1988;Nelson et al, 1980;Eastwood et al, 1982).…”
Section: Gij Feunekes Et Alsupporting
confidence: 87%
See 4 more Smart Citations
“…Associations in fat intake between parents and children as reported here were similar to some studies (Oliveria et al, 1992;Pe Ârusse et al, 1988;Lee & Kolonel, 1982;Eastwood et al, 1982) and high relative to other studies (Patterson et al, 1988;Laskarzewski et al, 1980;Nelson et al, 1980). Reported associations in fat intakes between husband and wives ranged between 0.38 and 0.58 in spouse pairs from North-America and the United Kingdom (Lee & Kolonel, 1982;Oliveria et al, 1992;Pe Ârusse et al, 1988;Nelson et al, 1980;Eastwood et al, 1982).…”
Section: Gij Feunekes Et Alsupporting
confidence: 87%
“…Parent-child associations in fat intake within families living together have only been reported from studies in North-America. The highest associations were found for Framingham mothers and their 3±5 y old daughters, r 0.35 to r 0.56 for the different fatty acids (Oliveria et al, 1992). Sta¯eu et al (1994) reported that resemblance in fat intake persists to some extent when parents and children do not live together any more; signi®cant associations were found between mothers and their 25 y old daughters, but not between the mothers and their mothers who were around age 75 y.…”
Section: Gij Feunekes Et Almentioning
confidence: 97%
See 3 more Smart Citations